Edukasi Pijat Bayi dengan Metode Demonstrasi dan Simulasi melalui Media Video di Kota Jambi - Armina, Armina; Nurfitriani, Nurfitriani; Irlandes, Ciria (Universitas Baiturrahim, 2025)
Baby massage is a gentle massage that is important for the growth and development of babies. Baby growth and development can be helped by baby massage. Posyandu Teratai V Legok has never conducted baby massage education and has been educated at the Putri Ayu Community Health Center in Jambi City. The purpose of this community service is to provide education about baby massage using video media. The implementation of this community service was carried out on May 8, 2024, held at Posyandu Teratai V in the working area of ​​​​Puskesmas Putri Ayu Jambi City. This activity targeted 10 mothers as participants, with a counseling method using videos and baby massage simulations. The implementation stage included a pre-test session, education, playing videos, baby massage simulations, and the evaluation stage in the form of a post-test session for skills in performing baby massage. The results of this Community Service were mothers enthusiastic in participating in the baby massage video education and gained knowledge after the education increased to an average score of 13 out of 7.9 and baby massage skills to an average score of 28.6 out of 4.1. The results of this Community Service can be continued at other Posyandu by training Posyandu cadres or Community Health Center officers.